2020
DOI: 10.1039/d0fo00208a
|View full text |Cite
|
Sign up to set email alerts
|

Pediococcus pentosaceusB49 from human colostrum ameliorates constipation in mice

Abstract: P. pentosaceus B49 partly normalized the expression of genes related to intestinal peristalsis, water and electrolyte absorption and transport, while down-regulating the expression of pro-inflammatory and pro-oncogenic genes in constipated mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Many P. pentosaceus strains isolated from different sources were proven to be linked with the human gastrointestinal tract [38]. In animal studies, P. pentosaceus strains have been reported that could improve acute liver failure, obesity, constipation, fatty liver, and intestinal inflammation [39][40][41][42][43]. In this study, we further revealed that a P. pentosaceus strain isolated from healthy children, CECT 8330, protected DSSinduced experimental colitis in mice as demonstrated by inhibition of weight loss, colon length shortening, and intestinal mucous damage.…”
Section: Discussionmentioning
confidence: 99%
“…Many P. pentosaceus strains isolated from different sources were proven to be linked with the human gastrointestinal tract [38]. In animal studies, P. pentosaceus strains have been reported that could improve acute liver failure, obesity, constipation, fatty liver, and intestinal inflammation [39][40][41][42][43]. In this study, we further revealed that a P. pentosaceus strain isolated from healthy children, CECT 8330, protected DSSinduced experimental colitis in mice as demonstrated by inhibition of weight loss, colon length shortening, and intestinal mucous damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that Akkermansia was reduced in patients with IBD, indicating that it may have potential anti-inflammatory effects [65], which was consistent with our study. Ruminococcaceae UCG-014 is an SCFA producer with an anti-inflammatory effect, which can protect the intestinal barrier and ameliorate colitis [66]. Recent studies found that probiotics and prebiotics administration increased the levels of the Lachnospiraceae NK4A136 group caused by DSS, which plays a critical role in relieving colitis [67].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with P. pentosaceus PP8 derived from the gut of juvenile whiteleg shrimp promoted many functions in whiteleg shrimp, such as digestive enzyme activity, disease resistance, growth and immunity. Isolated from human colostrum, P. pentosaceus B49 relieved constipation not only by improving gastrointestinal motility and water and electrolyte absorption but also by promoting neurotransmitter transmission and the growth of beneficial shortchain fatty acid-producing bacteria [69]. Isolated from rumen fluid, P. pentosaceus S22, with low carbohydrate tolerance, exhibited good adaptability to the gastric juice environment.…”
Section: Referencesmentioning
confidence: 99%
“…The interactions between P. pentosaceus and the gut microbiota alone have been widely analysed, but not many studies have evaluated them by -omics approaches, such as transcriptomics, proteomics, metagenomics, and 16S rDNA/rRNA gene sequencing. For example, gastrointestinal peristalsis was partially improved by treatment with P. pentosaceus B49, as determined by analysing the transcriptomic outcome in the colon [69]. The cell adherence function of P. pentosaceus GS4 was proved to produce a 98 kDa surface layer protein, as determined by proteomic technology such as SDS-PAGE and size exclusion chromatography [123].…”
Section: Probiotic Applicationsmentioning
confidence: 99%